Determinan Keberhasilan Usaha Mikro Kecil Menengah (UMKM) Pada Kecamatan Mandau - Winda Kusrianti; Endang Sri Wahyuni (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
The purpose of this study is to test the Influence of Business Location, Business Capital, Marketing Strategy and The Use of Accounting Information on the Success of MSMEs in Mandau District. This research is a type of quantitative research using primary data sources (questionnaires). The sampling technique uses the slovin formula, from the data obtained 326 respondents. Data analysis method using multiple linear regression analysis method with the help of IBM SPSS Statistics 23. The results of this study show that the calculated t value of each independent variable is 3,910 for location, 7,131 for business capital, 4,349 for marketing strategy and 2,792 for the use of accounting information, while the table t value is 2.242 (t calculate > t table) that means business location, business capital, Marketing strategies and the use of accounting information affect the success of MSMEs. This proves that the higher the business location, business capital, marketing strategy and the use of accounting information, the higher the success rate of MSMEs in Mandau District..Keywords: Business Location, Business Capital, Marketing Strategy, Usage Accounting Information, and MSME Success.